Bioinspired porous membranes containing polymer nanoparticles for wound healing. Issue 12 (25th February 2014) - Ferreira, Ana M.; Mattu, Clara; Ranzato, Elia; Ciardelli, Gianluca
Abstract Skin damages covering a surface larger than 4 cm2 require a regenerative strategy based on the use of appropriate wound dressing supports to facilitate the rapid tissue replacement and efficient self‐healing of the lost or damaged tissue. In the present work, A novel biomimetic approach is proposed for the design of a therapeutic porous construct made of poly(l‐lactic acid) (PLLA) fabricated by thermally induced phase separation (TIPS). Biomimicry of ECM was achieved by immobilization of type I collagen through a two‐step plasma treatment for wound healing. Anti‐inflammatory (indomethacin)‐containing polymeric nanoparticles (nps) were loaded within the porous membranes in order to minimize undesired cell response caused by post‐operative inflammation. The biological response to the scaffold was analyzed by using human keratinocytes cell cultures. In this work, a promising biomimetic construct for wound healing and soft tissue regeneration with drug‐release properties was fabricated since it shows (i) proper porosity, pore size, and mechanical properties, (ii) biomimicry of ECM, and (iii) therapeutic potential. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4394–4405, 2014.